Mitral valve bio-prosthesis and annuloplasty thrombosis during extracorporeal membrane oxygenation: case series. Issue 3 (24th April 2020) - Challa, Abhinay; Latona, Jilani; Fraser, John; Spanevello, Michelle; Scalia, Gregory; Burstow, Darryl; Platts, David
Abstract: Background: Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is a well-recognized form of haemodynamic support for patients with refractory cardiogenic shock, who are unable to be weaned off cardiopulmonary bypass. Thrombosis or bleeding from cannula sites or surgical wounds are the leading cause of morbidity and mortality in these patients, and presents a delicate balance of anticoagulation during management of patients undergoing circulatory support. Case summary: In this case series, we discuss three cases of patients undergoing mitral valve replacements or repair with thrombosis of their new bio-prosthesis in the immediate post-operative setting. All three patients were supported with VA-ECMO post-operatively, and thrombosis occurred despite anticoagulation. Discussion: During extracorporeal membrane oxygenation, the reduced flow throughout the heart increases the risk of intra-cardiac thrombosis. This is of particular importance in the context of mitral valve replacements and repairs, where the bio-prosthesis is an additional risk factor for thrombosis. Our cases demonstrate the morbidity and mortality of such complications, with the likely aetiology being low transvalvular flow in a newly inserted valve combined with the pro-thrombotic state created by the VA-ECMO circuit.